A tight binding study of electron transport in notched graphene nanoribbons - Mohamed R. Maamoon; A. M. Khalaf; M. Kotb; M. S. Sadeq; Mohammad A. Kher-Elden; Ignacio Piquero-Zulaica; Zakaria M. Abd El-Fattah (Scientific Reports)
Abstract Edge corrugated, notched graphene nanoribbons (GNRs) exhibit intriguing electronic properties distinct from their straight counterparts, thereby offering suitable candidates for the exploration of electron transport in future carbon-based nanoelectronic devices. Here, we utilize the tight binding (TB) method to investigate the electronic structure and quantum transport in gulf- and chevron-type notched GNRs. Consistent with earlier TB calculations, we reaffirm that the third-nearest neighbour hopping parameter is responsible for the electronic braiding effect and zero-energy conductance channels in straight zigzag GNRs (ZGNRs), here demonstrated for 2ZGNR and 5ZGNR. However, for notched gulf- or chevron-type GNRs, generated by selectively eliminating carbon atoms at either one or both ZGNR edges, the electronic band structures can be radically changed from semiconductor to metallic, with near-Fermi dispersive or flat bands. For the explored asymmetrically notched chevron-type GNRs hosting a metallic flat band at the Fermi energy, unlike straight ZGNRs, the electronic transport was found to depend primarily on the second-nearest neighbour, exhibiting a sharp conductance peak (of 1 unit conductance) at the Fermi energy. This result is found to be generic for all asymmetric chevron-type GNRs, irrespective of the nanoribbon width, and also for edge-notched armchair GNRs hosting similarly metallic flat bands. For the metallic symmetrically notched chevron-type GNR, however, the near-Fermi dispersive bands lead to multiple conductance channels around the Fermi energy, with fine structure dependence on the number of hopping parameters utilized. These results are analyzed with respect to the spatial distribution of the metallic states and how they transverse across the ZGNR leads. The present study should have large implications on the exploration of electronic transport in carbon-based nanoelectronic devices.